Efektivitas Prinsip 3R dalam Pengelolaan Sampah Berdasarkan Peraturan Daerah Nomor 4 Tahun 2021 Tentang Pengelolaan Sampah : Desa Tanjung Selamat Kecamatan Sunggal - Dandi Putra Bintang; Arief Wahyudi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to analyze the effectiveness of the implementation of Regional Regulation Number 4 of 2021 in waste management in Tanjung Selamat Village, Sunggal District, Deli Serdang Regency, and to identify factors influencing the success and failure of the 3R (Reduce, Reuse, Recycle) principle in the area. This study uses a qualitative descriptive approach with data collection techniques through observation, in-depth interviews, and documentation. The research subjects included Village Officials, Community Self-Help Groups (KSM), and residents of Tanjung Selamat Village. The collected data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results show that the implementation of the 3R principle in Tanjung Selamat Village has not been running optimally and still faces various obstacles. The effectiveness of waste management through the 3R approach is hampered by low community participation, limited facilities and infrastructure, weak supervision and law enforcement, and uneven socialization. However, several factors support the successful implementation of the 3R principle, such as the existence of continuous socialization and education activities, active involvement between the village government and local communities, the provision of supporting facilities, and the implementation of recycling programs by community groups. This study recommends increasing community participation, strengthening inter-agency coordination, and expanding outreach to ensure more effective and sustainable implementation of the 3R principles at the village level.